Analisis Pengelolaan Laboratorium Fisika di MAN 1 Rokan Hulu - Nurhikmah Sasna Junaidi; Rindi Genesa Hatika; Dahlia Dahlia; Untung Hasibuan (Pendidikan Fisika UIN Alauddin Makassar, 2023)
This study aims to analyze the quantity and quality of equipment, furniture and laboratory space as well as administrative management, personnel and security of the MA physics laboratory in MAN 1 Rokan Hulu. The research was conducted using descriptive quantitative data collection techniques by distributing questionnaires and observations. Data analysis techniques in the descriptive method depend on the logical thinking and imagination of the researcher. The results showed that the physics laboratory room at MAN 1 Rokan Hulu did not meet the minimum standards for the area of ​​the lab with a minimum of 36 students, for the width of the lab, the area of ​​the storage room and the dark room had met the minimum standards. facilities and infrastructure with an average of 89.05% are categorized as very good, in terms of laboratory personnel management with a presentation of 72.65%. The qualifications of the laboratory staff expertise are categorized as good with an average of 66.66%. The Physics Laboratory of MAN 1 Rokan Hulu based on the category studied and in the school includes laboratories in the Good category.